Regulatory implications of 2007 financial crisis and the effect of financial regulation structures on the soundness of banking sector: a cross-country perspective - Gümüş, Nihat. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This study is related to the regulatory implications of 2007 Financial Crisis and the effect of financial regulation structures on the soundness of banking sector. Depending on qualitative analysis of reports published by international and national authorities, the study extracts seven broad regulatory issues that are highlighted by 2007 Financial Crisis. Moreover, the study includes an empirical analysis using financial data of 486 banks from 7 counties, namely the USA, the UK, Germany, France, Italy, the Netherlands, and Australia, to explore the effect of financial regulation structures on banking sector soundness. The data covers the period from 2002 to 2009. ANOVA and Logistic regression results suggest that regulation structures have an impact on the soundness of the banking sector. The governments should also consider the diversity of services provided by financial institutions and country-specific factors when designing regulatory structures. Main contribution of the study is twofold. Firstly, it presents a composite picture of regulatory issues discussed at global level after 2007 Financial Crisis. Secondly, it provides empirical evidence related to the relationship between financial regulation structures and the soundness of financial system.
Keywords: Global Financial Crisis, 2008-2009.; Financial crises.; International finance.; Banks and banking.